DEVELOPMENT SCIENTIFIC INQUIRY BASED TEACHING MATERIALS ON DYNAMIC FLUIDS TO IMPROVE STUDENTS ACHIEVEMENT - Jeliana Veronika Sirait; Nurdin Bukit; Makmur Sirait (Universitas Negeri Medan, 2016)
The study was conducted to investigate whether the developed scientific inquiry-based teaching materials can improve the students’ response, the students’ activity and the students’ achievement. This study is development which based on Borg & Gall product development. Samples were selected randomly by raffling 4 classes into one class, applied teaching materials based scientific inquiry. The instruments which are used in this study consisted of three namely quetionnaires used for validation of teaching material by the expert of the material and the expert of design, the evaluation of physics teacher and students’ response toward teaching materials and observation sheet of students’ activity used in learning process and also test for students’ achievement in the form of multiple choice consisted of 10 quetions provided for end of the learning. The results of this study showed that the developed scientific inquiry-based teaching materials can improve the students’ response, the students’ activity and the students’ achievement in every session.